If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X(6+X)-2(X+1)-5X=4-2.0
We move all terms to the left:
X(6+X)-2(X+1)-5X-(4-2.0)=0
We add all the numbers together, and all the variables
X(X+6)-2(X+1)-5X-2=0
We add all the numbers together, and all the variables
-5X+X(X+6)-2(X+1)-2=0
We multiply parentheses
X^2-5X+6X-2X-2-2=0
We add all the numbers together, and all the variables
X^2-1X-4=0
a = 1; b = -1; c = -4;
Δ = b2-4ac
Δ = -12-4·1·(-4)
Δ = 17
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-\sqrt{17}}{2*1}=\frac{1-\sqrt{17}}{2} $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+\sqrt{17}}{2*1}=\frac{1+\sqrt{17}}{2} $
| 19x+3+40=180 | | a-3=-6a-10 | | −2x=−15 | | 2-1/3u=5/3u+6 | | 533=265+48x | | 15=3/4x-7 | | x-7÷5=8 | | 5x-18x=13 | | -8-4v=-7-3(v+3) | | -109=7x-8(8-x) | | -6-6v=-1-7v | | 25+42.95x=60+42.95x | | 60t=59 | | 60*t*t*t=59 | | 3(2x+5)=-37+34 | | 2x-1(6)=13 | | 60*t*t*t/60=1 | | 6(7n+6)=-258 | | 23x-14=7x+82 | | 3+x+3x=x+6 | | 59=-13+4u | | 8x-10=6x-20 | | 2(8+6p)=88 | | k-2=7k+16 | | 7x-5=3x^2+2x-1 | | 4x/5-3/10=7 | | 5(n+4)=12-n | | -12/7x=48 | | 7/4x=59/12 | | 17+3q=-25 | | 4-x+3x=7x-1 | | 2-3s+5s=5 |